Exploring the importance of logistics in the strategic business decisions of Bulgarian SMEs - Ivan Dimitrov; Emanuila Antonova; Adile Dimitrova (Entrepreneurship and Sustainability Issues)
Business without logistics? That is no longer a question in present-day entrepreneurship; small businesses are no exception. Logistics evolved into a workable business function in corporate strategy, and what nowadays could split the involved group of researchers and managers is only their consideration of logistics weight in a successful business formula. Small business entrepreneurs are challenged to place the mark for the limit of logistics importance properly. Small businesses seeking to ensure a safe place in a competitive supply chain need to evaluate the significance of logistics for their success. The centre of attention of this research is the logistics notability amongst other functional areas in the strategic business decisions for Bulgarian SMEs. The reasons to make or buy logistics have been analysed through criteria tools focusing on financial performance, business priorities and service elasticity for the thorough satisfaction of stakeholders. The research project aims to explore the importance of logistics for small enterprises through a quantitative assessment of logistics elements in Bulgarian examples. The primary research outcome is joined to the affirmation of scientific hypotheses about the crucial level of logistics transaction and translation costs, logistics outsourcing ratio, business flexibility, the leading factors for partnership and market impact for Bulgarian SMEs. Through a standardised questionnaire approach and data processing to regression multilinear analysis, valuable information is obtained that may influence the successful decision-making of Bulgarian professionals. In-vivo findings ex genuine business could be promoted amongst educational studies to teach future experts in management and economics with an accent on the area’s business-specific conditions.